Os princípios políticos e a prática educativa do CESEP: processos formativos de uma ONG em Sergipe: 1988/1998 - Figuerêdo, Acácio Nascimento (2003)
This study analyses the Political Principles and the Educational Practice of Centro Sergipano de Educação Popular (CESEP) from 1988 to 1998. As well as its institutional nature, its social political role of formation of social movements in Sergipe, and of support for these movements. It interprets the Social Movements, Social Class and Work as explanatory categories for the investigated object. The reseach focuses on the formative processes developed in the educational programs of this NGO`s. In order to accomplish this, it starts with the interpretation of the NGO`s in the context of globalization, emphasising that in Latin America, Brazil, and especially in the Northeast, the apogee of the neo-liberalism, in the 1990`s, determined the new ways of social policies. The work follows the principles of Historical Science in the patterns of Critical-Historical Pedagogy. The conclusion is that CESEP reveals itself as an institution in tune with the neo-liberalism precepts when it comes to its insertion in the global movement proper to the NGO`s, moreover, it presents advances towards the transmission of an Education towards Citizenship , although it is still based on concepts of social rights in the liberal patterns.